SnO 2 ceramics with low electrical resistivity obtained by microwave sintering - Gasparotto, Gisane [UNESP]; Bordignon, M. A N [UNESP]; Foschini, C. R. [UNESP]; Gasparotto, Gisele [UNESP]; Aguiar, E. C. [UNESP]; Zaguete, M. A. [UNESP]; Perazolli, L. [UNESP] (American Scientific Publishers, 2011)
The main aim of this study was to develop dense and conducting SnO 2 ceramics without precipitated phases on the grain boundaries, which was verified using field emission scanning microscopy (FE-SEM) coupled with an energy-dispersive X-ray spectroscopy (FE-SEM/EDS). Two sample groups were investigated, where the first sample group was doped with zinc while the second one was doped with cobalt. The ceramics were prepared using the oxides mixture method and the sintering was carried out in a conventional muffle oven as well as in microwave oven. The results obtained were found to be similar regarding the relative density for the two sintering methods while time and temperature gains were observed for the microwave sintering method. The relative densities obtained were nearly 95%, for the two sintering methods. Concerning the electrical characterization measurements-electric field x current density as well as the environment temperature, the ceramics obtained through the conventional sintering method presented non-ohmic behavior. For the microwave sintered ceramics, we observed an ohmic behavior with electrical resistivity of 1.3 Ωcm for the samples doped with ZnO/Nb 2O 5 and 2.5 Ωcm for that of the samples doped with CoO/Nb 2O 5. The FE-SEM/EDS results for the microwave sintered ceramics indicated a structure with a reduced number of pores and other phases segregated at the grain boundaries, which leads to a better conductive ceramic than the conventional oven sintered samples. The dilatometry analysis determined the muffle sintering temperature and the difference between the densification of cobalt and zinc oxides. The addition of niobium oxide resulted in the decrease in resistivity, which thus led us to conclude that it is possible to obtain dense ceramics with low electrical resistivity based on SnO 2 using commercial oxides by the oxides mixture technique and the microwave oven sintering method. Copyright © 2011 American Scientific Publishers All rights reserved.
Keywords: Aluminium production; Cobalt oxide; Electrical characterization; Microwave oven; Niobium oxide; Sintering; Tin oxide; Zinc oxide; Cobalt oxides; Conductive ceramics; Conventional ovens; Conventional sintering; Dense ceramics; Dilatometry; Electrical resistivity; Energy dispersive x-ray spectroscopy; Environment temperature; Field emission scanning; Microwave sintering; Mixture method; Nonohmic behavior; Ohmic behavior; Relative density; Sintered ceramics; Sintered samples; Sintering temperatures; ZnO; Ceramic materials; Cobalt; Electric conductivity; Electric fields; Energy dispersive spectroscopy; Grain boundaries; Microwave heating; Microwave ovens; Tin; Tin oxides